A STUDENTS 'LEARNING INTEREST IN LEARNING E-LEARNING CLASS VA IN MIN 1 TUBAN: MINAT BELAJAR SISWA TERHADAP BELAJAR E-LEARNING KELAS VA MIN 1 TUBAN - Mahiroh, Ani Satul (Journal Of Islamic Elementary School (JIES), 2025)
ABSTRACT This study aims to determine how the students' interest in learning e-learning. The indicators of interest in learning studied were a feeling of pleasure in e-learning learning, comfort in using e-learning, and positive feelings obtained in e-learning learning. This study used a qualitative approach by distributing questionnaires to class V-A students of MIN I Tuban and interviewing class teachers to obtain data. The results of this study indicate that the students' interest in learning class V-A MIN I Tuban in e-learning is very high. However, the lack of facilities and infrastructure (cell phones and internet quotas) and parents who do not master e-learning become obstacles in learning using e-learning. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana minat belajar siswa dalam pemebelajaran e-leaerning. Indikator minat belajar yang diteliti adalah perasaan senang terhada pembelajaran e-learning, kenyamanan dalam penggunaan e-learning, dan perasaan positif yang diperoleh dalm pembelajaran e-learning. Penelitian ini menggunakan pendekatan kualitatif dengan menyebar angket pada siswa kelas V-A MIN I Tuban dan wawancara guru kelas untuk memperoleh data. Hasil dari penelitian ini menunjukkan bahwa minat belajar siswa kelas V-A MIN I Tuban dalam pembelajaran e-learning sangat tinggi. Akan tetapi, kurangnya sarana dan prasarana (HP dan kuota internet) serta orangtua yang kurang menguasai e-learning menjadinkendala dalam pembelajaran menggunakan e-learning.